When Change Matters: An Analysis of Survey Interaction in Dependent Interviewing on the British Household Panel Study - Uhrig, SC Noah; Sala, Emanuela (Sociological methods & research, 2011)
The authors examine how questionnaire structure affects survey interaction in the context of dependent interviewing (DI). DI is widely used in panel surveys to reduce observed spurious change in respondent circumstances. Although a growing literature generally finds beneficial measurement properties, little is known about how DI functions in interviews. The authors systematically observed survey interaction using behavior coding and analyzed an application of DI to obtain respondent employment characteristics. The authors found respondents indicated change in circumstances through a number of verbal machinations, including mismatch answers and explanations. Assessing whether these behaviors influenced subsequent question administration, the authors found qualitative evidence that the information disclosed when negating a DI question leads to subsequent interviewing errors. Quantitative analyses supported this evidence, suggesting that standardized interviewing deteriorates as respondents struggle to identify change in their circumstances. This analysis suggests that the reliability of detail about changed circumstances may not be improved using DI.